Respuesta :

Answer:

Step-by-step explanation:

Combine like terms. Like terms have same variable with same power

a) (2xy + 4x) + (15xy - 5x)  = 2xy + 15xy + 4x - 5x

                                         = 17xy - x

b) (6a + 4b² - 3) + (3b² - 5) = 6a + 4b² + 3b²  - 3 - 5

                                           = 6a + 7b² - 8

c) (4x³ - 3x² +4x) + (8x² - 5x ) = 4x³ - 3x² + 8x²  + 4x - 5x

                                               = 4x³  + 5x² - x

d) (7b - 6a  + 9y) - (12b + 5a - 2y) =

In subtraction, add the additive inverse of (12b + 5a - 2y)

additive inverse = - 12b  - 5a  + 2y

(7b - 6a  + 9y) - (12b + 5a - 2y) = 7b - 6a + 9y  -12b -5a + 2y

                                                   = 7b - 12b  -6a - 5a  + 9y + 2y

                                                   = -5b - 11a + 11y

e) (2x² + 7x - 2 + 9y) - (13x + 4x² + 5 - 6y)

Additive inverse of  13x + 4x² + 5 - 6y = -13x + 4x² - 5 + 6y

(2x² + 7x - 2 + 9y) - (13x + 4x² + 5 - 6y)= 2x² + 7x - 2 + 9y -13x - 4x² -5 +6y

                    = 2x² - 4x² + 7x -13x -2 - 5 + 9y + 6y

                    = -2x²  - 6x  - 7 + 15y